Direct Inhibition of Microglia Activation by Pretreatment With Botulinum Neurotoxin A for the Prevention of Neuropathic Pain - Feng, Xiaona; Xiong, Donglin; Li, Jie; Xiao, Lizu; Xie, Weijiao; Qiu, Yunhai (Frontiers in Neuroscience, 2021)
Peripheral injection of botulinum neurotoxin A (BoNT/A) has been demonstrated to have a long-term analgesic effect in treating neuropathic pain. Around peripheral nerves, BoNT/A is taken up by primary afferent neurons and inhibits neuropeptide release. Moreover, BoNT/A could also be retrogradely transported to the spinal cord. Recent studies have suggested that BoNT/A attenuates neuropathic pain by inhibiting the activation of spinal glial cells. However, it remains unclear whether BoNT/A directly interacts with these glial cells or via their interaction with neurons. Our aim here is to determine the direct effect of BoNT/A on primary microglia and astrocytes. We show that BoNT/A pretreatment significantly inhibits lipopolysaccharide (LPS) -induced activation and pro-inflammatory cytokine release in primary microglia (1 U/mL BoNT/A in medium), while it has no effect on the activation of astrocytes (2 U/mL BoNT/A in medium). Moreover, a single intrathecal pre-administration of a low dose of BoNT/A (1 U/ kg) significantly prohibited the partial sciatic nerve ligation (PSNL)- induced upregulation of pro-inflammatory cytokines in both the spinal cord dorsal horn and dorsal root ganglions (DRGs), which in turn prevented the PSNL-induced mechanical allodynia and thermal hyperalgesia. In conclusion, our results indicate that BoNT/A pretreatment prevents PSNL-induced neuropathic pain by direct inhibition of spinal microglia activation.